The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1046/j.1365-2567.1996.431546.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress triggers tyrosine phosphorylation in B cells through a redox‐ and inflammatory cytokine‐sensitive mechanism

Abstract: SUMMARYExposure to oxidants such as hydrogen peroxide (H 2 O 2 ) and g -ray irradiation has been recently shown to trigger tyrosine phosphorylation in B cells as does cross-linking surface immunoglobulin (sIg) by antigens or anti-immunoglobulins. We studied the mechanism by which H 2 O 2 induced tyrosine phosphorylation in B cells and compared it with the mechanism utilized by sIg. Both antiimmunoglobulin M (anti-IgM) and H 2 O 2 induced tyrosine phosphorylation through protein tyrosine kinase (PTK) activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Reactive oxygen species such as hydrogen peroxide (H 2 O 2 ) activate the Akt serine/threonine kinase; however, little is known concerning the effects of oxidant treatment of cells on the regulation of PDK1, the activating kinase for Akt. Since hydrogen peroxide has been reported to stimulate tyrosine phosphorylation of signaling proteins in a number of cellular systems (3,(7)(8)(9)(10)(11)(43)(44)(45)(46)(47)(48)(49), we investigated the effects of H 2 O 2 on tyrosine phosphorylation of PDK1. Initial experiments were performed using 293T cells transiently expressing myctagged PDK1.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species such as hydrogen peroxide (H 2 O 2 ) activate the Akt serine/threonine kinase; however, little is known concerning the effects of oxidant treatment of cells on the regulation of PDK1, the activating kinase for Akt. Since hydrogen peroxide has been reported to stimulate tyrosine phosphorylation of signaling proteins in a number of cellular systems (3,(7)(8)(9)(10)(11)(43)(44)(45)(46)(47)(48)(49), we investigated the effects of H 2 O 2 on tyrosine phosphorylation of PDK1. Initial experiments were performed using 293T cells transiently expressing myctagged PDK1.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, proteins that are abnormally synthesized or modified post-translationally are often targeted for ubiquitination (42,60). Since TNF␣ alters oxidant tone within cells (62), it is possible that oxidation of CCT methionine residues, or other post-synthetic modifications such as serine phosphorylation, or alterations in NH 2 -terminal protein folding could destabilize the enzyme facilitating incorporation into the ubiquitin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Since neutrophils are one of the main sources of IL10 and of IL12 (Romani et al 1997), accumulation of neutrophils may aect the determination of the balance governing Th1 and Th2 cell development at the local site. Furthermore, it was reported that neutrophil-derived oxidants possibly mediate the activation of tyrosine phosphorylation or transcriptions of in¯ammatory cytokines by releasing of the inhibitory subunit I kappa B from NF-kappa B (Suzuki et al 1996). This potentially increases the cytokine production and growth signalling pathways of T cells (Ferreira et al 1999).…”
Section: Discussionmentioning
confidence: 99%